Video Teaching Demonstration and Final Examination: Supplementary Files - Bonnewell, Tiffany M. (My University, 2018)
In the lesson clip shown, students are learning to count rhythms containing rests using the Eastman counting method. The learning target is to prepare students to "count sing" during rehearsals in their advanced choir next school year.
Keywords: Music; Education; Teaching; Demonstration; Scaffolding